DESIGN AND NUMERICAL ANALYSIS OF A VEHICLE ARMOUR AGAINST BULLETS AND SHAPED CHARGES - (:unkn) unknown (AMER SOC MECHANICAL ENGINEERS, 2016)
Armored vehicles are used to carry soldiers and machinery in combat environment in safety. As a result of the experience of a military force involved in the missions in combat areas, armoring of military-vehicle should be durable against bullet impacts and shaped charge explosions. These vehicles should provide required protection of soldiers and equipment against penetration and explosion and also have good mobility (moveable capability). In order to achieve this, the vehicle must be lightweight. The most suitable material should be selected and the most suitable geometry should be designed to achieve this goal. In this study; different material combinations and different geometries are simulated using the finite element method and smooth particle hydrodynamics. Different caliber bullets are impacted into armor and their penetration affects are observed. Shaped charge explosive also used. As a result of this simulation, the material combinations are optimized to achieve the best armor.